PENGARUH JUMLAH UANG BEREDAR DAN PENGELUARAN PEMERINTAH TERHADAP PRODUK DOMESTIK BRUTO (PDB) INDONESIA - Tambunan, Sely Nory; Yusuf, Yusbar; Mayes, Anthoni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research aimed to determine the effect of the Money Supply and Public Spending Against Domestic Product of Indonesia. This study uses secondary data from the 1998-2012 time series obtained from the offices of Bank Indonesia (BI) and the Central Bureau of Statistics (BPS). The method of analysis used in this research multiple linear regression analysis using SPSS version 21. This research consists of two independent variables, namely the Money Supply and Government Expenditure and the dependent variable is the Indonesian Gross Domestic Product. Based on the calculation results obtained Fhitung value of 700.991 with a significant level of 95% (α = 0.05) and Ftabel value of 3.89. So, Fhitung (700.991)> Ftabel (3.89). So it can be concluded that the Money Supply and Government Expenditure simultaneously or jointly influence on Indonesia's Gross Domestic Product. Partially Money Supply and Government Expenditure has a significantly positive influence on Indonesian Gross Domestic Product. Based on the research results of the calculation, the value of R quad is 0.990. This means that 99.00% of ross Domestic Product in Indonesia is affected by the Money Supply and Government Expenditure, while 10% are influenced by other factors that are not addressed in this study.Keywords: Money Supply, Government Expenditure and Gross Domestic Product (GDP) of Indonesia.